Penerapan Pembelajaran Game Interaktif Di SDN 09 Buatan Baru Kecamatan Kerinci Kanan - Siswanto Siswanto; Nurman Efrinson Tamba; Diva Natasha Putri; Erni Maulidiawati; Tasya Fajar Putri; Amanda Tifani; Filma Anggraini; Anis Aprilia; Yulu Yanti Sitompul; Donny Lukfiansah; Jordan Napitupulu (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Interactive learning media is an intermediary that can help in the learning process, so that learning becomes fun. one of these learning media is game-based. which aims to provide an atmosphere in the teaching and learning process that is more enjoyable with mutual activity between educators and their students. in this activity carried out at SDN 09 buatan baru school with the style of the game link dots, in the implementation, several tables are given that contain some material that is connected with color dots, as the game link dots.